Environment, Social, Governance (ESG) Factors And The Impact On Market Value Added (MVA) For Malaysian Public Listed Companies - Lim, Mayyi (2022)
There is confusion on many market standards when environmental, social, and governance (ESG) topics recently increased awareness among countries and companies. However, the ESG catalysts and market analysts widely prefer the Bloomberg database on the ESG score. Hence, this study explores the impact of ESG factors on market value added (MVA) among the public listed companies in Malaysia. A sample size of 90 public listed companies from Bursa Malaysia listed under the main market, ACE market and LEAP market for nine years, from 2012to 2020, which resulted in 810 observations. The partial least squares structural equation modelling (PLS-SEM) and confirmatory factor analysis are utilized as the research methodologies of this study. The analysis revealed that the Bloomberg ESG score has a positive but no significant relationship with Market Value Added (MVA). Only 90 out of 967 public listed companies in Bursa Malaysia have the ESG score, which results in the overall insignificant of the ESG score on the firm’s MVA.